Collaborative study for the calibration of the replacement International Standard for pertussis toxin for use in histamine sensitisation and CHO cell clustering assays. (November 2019) - Douglas-Bardsley, Alexandra; Asokanathan, Catpagavalli; Tierney, Sharon; Hockley, Jason; Markey, Kevin
Abstract: Pertussis toxin (PT) in its detoxified form is one of the major protective antigens in vaccines against Bordetella pertussis (whooping cough). Reference preparations of native PT are required for the quality control of pertussis vaccines. Stocks of the first WHO International Standard (IS) for PT (JNIH-5) were low and a replacement was required. One candidate material was donated by a vaccine manufacturer to NIBSC. It was formulated, lyophilised into sealed glass ampoules and coded 15/126. An international collaborative study assessed the suitability of this material to replace JNIH-5. Fourteen laboratories from 12 countries took part in the study. Eleven laboratories performed lethal murine histamine sensitisation assay (HIST), 14 performed Chinese Hamster Ovary (CHO) cell clustering assay. International Units (IU) were assigned to the material using these assays as they were used to assign units to JNIH-5. It was found that, unlike JNIH-5, the activities of 15/126 in HIST and CHO cell assays did not agree and therefore different unitage for each assay was assigned. The preparation 15/126 was established as the Second WHO IS for PT for HIST and CHO cell assays. It was assigned a unitage of 1, 881 IU/ampoule in HIST and 680 IU/ampoule in the CHO cell clustering assay.